1987
DOI: 10.3168/jds.s0022-0302(87)80017-6
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Effect of β-Carotene in Diet on Fertility of Dairy Cows

Abstract: A total of 155 high yielding dairy cows were used to study the effect of dietary beta-carotene (carotene) on fertility. The diet of group 1 was supplemented with 69 mg retinyl acetate per cow daily before calving and 96 mg retinyl acetate after calving: diet of group 2 was supplemented with 500 mg carotene per cow before calving and 96 mg retinyl acetate after calving; and that of group 3 with 500 mg carotene before and 700 mg after calving. Conception rates were 53.9, 42.2, and 27.9% for cows of groups 1, 2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 13 publications
3
13
0
Order By: Relevance
“…It is also observed that the higher concentrations of ß-carotene used tended to be more suppressive as compared to 1 10"7 M, suggesting possible toxic effects (see Hey wood et al, 1985). These results agree with those reported by Folman et al (1987) in which the intake of high ß-carotene seemed to have an adverse effect on fertility of dairy cows.…”
Section: Discussionsupporting
confidence: 95%
“…It is also observed that the higher concentrations of ß-carotene used tended to be more suppressive as compared to 1 10"7 M, suggesting possible toxic effects (see Hey wood et al, 1985). These results agree with those reported by Folman et al (1987) in which the intake of high ß-carotene seemed to have an adverse effect on fertility of dairy cows.…”
Section: Discussionsupporting
confidence: 95%
“…While an optimal intake of BC is hypothesized to have positive effects upon reproductive outcomes both in ruminant (Arellano-Rodriguez et al 2007) and monogastric (Krammer and Aurich 2010) species, results have been contradictory, with studies reporting both positive (Kawashima et al 2009(Kawashima et al , 2012 and negative (Folman et al 1987) effects. Nonetheless, a positive relationship between BC supplementation, metabolic and endocrine status as well as reproductive outcomes has been previously proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Positive responses in dairy cow fertility and lactation performance have been observed when β-carotene was supplemented after calving (Aréchiga et al, 1998;De Ondarza et al, 2009), although absent (Bindas et al, 1984;Akordor et al, 1986) or negative (Folman et al, 1987) effects on reproduction have been reported. Kaewlamun et al (2011) and Wang et al (2013) have reported benefits in uterine health of cows supplemented with β-carotene before calving.…”
Section: Introductionmentioning
confidence: 94%